A PROSPECTIVE OBSERVATIONAL STUDY OF THE CLINICAL PREVALENCE OF RETINOPATHY OF PREMATURITY IN PRETERM INFANTS AT A HOSPITAL IN ODISHA. - Mali, Bijoy Kumar; Behera, Sharmistha; Sunanda, Rangumudri Sai; Patra, Saumya Ranjan; Mishra, Pradyumna; Sahu, Sasmita (Student’s Journal of Health Research Africa, 2024)
Background Retinopathy of prematurity (ROP), the scar tissue behind the neonate lens associated with retinal detachment, has been responsible for the two largest ‘epidemics’ of blindness in neonates in modern times. There is a rise in such cases reported around the world. However, ROP is preventable with advanced techniques. This study is carried out to determine the epidemiological profile of ROP Method This was a prospective observational study carried out at the Department of Ophthalmology and Neonatal Intensive Care Unit Veer Surendra Sai Institute of Medical Sciences and Research Centre, Burla, Sambalpur, Odisha for a period of two. Infants with lesser birth weight and preterm were considered for the study. The demography of the infants, along with oxygen therapy and the other required treatments were recorded. The eyes of the infants were examined with RetCam. Retinopathy was graded into Zone and Stages as per ICROP classification. Those infants with retinopathy were further examined and those with proper vascularization were not examined. Results Overall 268 infants were included in this study. The occurrence of ROP was 45.9%. The infants with less than 1000 grams, gestational age between 26-30 weeks, had sepsis, had RDS, were IVH, had anemia, and received supplemental oxygen were prone to ROP. Zone II was the most affected zone and the ROP was at stage I and II IN most of the infants. Conclusion The risk factors associated with the occurrence of ROP include gestational age, birth weight, RDS, anemia, sepsis, IVH, RDS, and supplemental oxygen. Proper screening is required for diagnosis of occurrence ROP. Recommendation The risk factors discussed in the study should be considered for preterm babies and necessary screening should be done. Early diagnosis can prevent blindness in infants